Scenario planning : a field guide to the future - Wade, Woody (Wiley, 2012)
"Is your business ready for the future? Scenario planning is a fascinating, yet underutilized, business tool that can be of immense value to a company's strategic planning process. It allows companies to visualize the impact that a portfolio of possible futures could have on a company's fortunes. It helps decision-makers see opportunities and threats that could emerge beyond their normal planning horizon. Scenario Planning serves as a guide to the looking at your business, and the world, years from now, posing thoughtful questions about the possible consequences of some current (and possible future) trends. This book will help you: Outline (and help you prepare for) any trends that could play out in the future that change the political, social, and economic landscapes and significantly impact your business Explore the impact of technological advances and newly available products to your business Examine challenges that are only dimly recognizable as potential problems today This visual book will help you answer this question: Is my organization ready for every possibility?"--